2022
DOI: 10.21474/ijar01/14017
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Clinical Profile of Pericardial Effusion Patients

Abstract: Background Pericardial effusion is one of the most prevalent disorders . Pericardial effusion can create substantial symptoms and a lower quality of life, but its also linked to a higher risk of cardiopulmonary failure, mortality, and death. Pericardial effusion has a variety of causes that are related to the relative occurrence of certain diseases in different parts of the world. Methods:it was a retrospective study that includes data from all pericardial effusion cases diagnosed . Echocardiography was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Khanal, R. et al 9 also reported most common etiology to be tuberculosis (36.5%) followed by malignancy (19%) and idiopathic/Viral (12.6%). Bista, M et al 10 and Ahmed Wani, O. et al 11 also reported Tuberculosis to be the major cause of Pericardial effusion. The second most common cause was heart failure.…”
Section: Discussionmentioning
confidence: 96%
“…Khanal, R. et al 9 also reported most common etiology to be tuberculosis (36.5%) followed by malignancy (19%) and idiopathic/Viral (12.6%). Bista, M et al 10 and Ahmed Wani, O. et al 11 also reported Tuberculosis to be the major cause of Pericardial effusion. The second most common cause was heart failure.…”
Section: Discussionmentioning
confidence: 96%